Integral Backstepping Control for Stabilizing an Underactuated X4-AUV - Nur Fadzillah, Harun; Zainah, Md. Zain (2015)
Autonomous Underwater vehicles (AUV) is one of an unmanned underwater vehicle (UUV) that work independently and can be control automatically on board without requiring a cable. The autonomous capability has great important tasks due to navigate in abyss zones and dangerous underwater mission. However, in order to stabilize the system consists of four control inputs and six degree of freedoms (DOFs) is difficult tasks because of the nonlinear dynamic and model uncertainties. This paper presents the stabilization of underactuated X4-AUV using nonlinear control techniques, integral backstepping. The key idea of integral backstepping is to design a virtual controller for each subsystem by associate with integral of tracking error. The effectiveness of the proposed control technique demonstrates by simulation.